(untitled) (Revista Iberoamericana de Bioética, 2018)
The patient needs comprehensive care in the field of health, including in religious aspects. Today, the extremist positions that wish to expel the religious to the realm of private seem to have been overcome. But nor are wholly irrational religious positions acceptable. Tracks of dialogue for the integration of both realities, the religious and the non-religious, are offered, presenting some of the contributions theology can offer and pointing out some of the challenges faced in continuing to build good relations based on dialogue and the common search.